2021
DOI: 10.48129/kjs.15051
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Global Solar Radiation from Sunrise Duration Using Regression Functions

Abstract: The paper estimates the global solar radiation in Dubai and Abu Dhabi meteorological stations in the United Arab Emirates. Theoretical models based on Angstrom-Prescott have been applied on data of sunshine hours for the period from 2010 to 2019. The models are developed using 2010 - 2018 data and validated by comparing to the 2019 data. Theoretical solar radiation estimates the maximum of global solar radiation to be in June for both stations, which is in good agreement with the actual data. The performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…According to previous investigations, a triangular 2D foam of ideally six-fold coordination remained metastable for a short period of time before collapsing. One defect allowed the foam to maintain its stability in this respect despite the introduction of another 11,12) .…”
Section: Methodsmentioning
confidence: 99%
“…According to previous investigations, a triangular 2D foam of ideally six-fold coordination remained metastable for a short period of time before collapsing. One defect allowed the foam to maintain its stability in this respect despite the introduction of another 11,12) .…”
Section: Methodsmentioning
confidence: 99%
“…However, although some studies including Ismail, (2022) 36) used regression functions such as the root mean square error (RMSE) and mean bias error (MBE) to evaluate the statistical Angstrom-Prescott model, it is beyond the scope of the present study to conduct such studies as the Angstrom-Prescott could be able to show reasonable results when compared to measured data from NASA as well as the regression functions as shown respectively in Hassane, et al (2018) 12) and Ismail, (2022) 36) .…”
Section: Analysis Methodology and Formulationmentioning
confidence: 99%
“…Meteorological factors, including dawn duration, temperature, and RH, have been used to assess solar radiation at various places. The study showed that higher levels of air pollution were associated with increased solar radiation, which was the greatest during the summer [54][55][56]. PM concentration using a LCS as a detector showed positive R 2 with a reference device [57,58].…”
Section: Introductionmentioning
confidence: 99%